FACTORS INFLUENCING THE USE OF COMMUNICATION STRATEGIES BY ENGLISH AS AN ADDITIONAL LANGUAGE LEARNERS: A NARRATIVE REVIEW - Afifah Muharikah (Politeknik Negeri Jakarta, 2022)
This review study identified factors that instructors of English as an additional language (EAL) could consider when designing peer interaction-based activities to promote learners' use of effective communication strategies (CSs). In addition, we investigated how the identified factors might benefit inclusive EAL classrooms where learners with special needs participate in peer interactions. This review study aimed to equip EAL instructors with information that could be considered to promote the use of effective CSs by learners in the classroom. To follow the guidelines of the narrative literature review method outlined by Green et al., (2006), articles were extracted from the ERIC, Linguistics, Education, and Arts and Humanities databases, and the information from the articles was reviewed to answer two research questions. Our review identified two factors that EAL instructors should consider: the personal factors of learners and the types of tasks. The first factor includes learners' levels of proficiency, level of anxiety, as well as self-efficacy, learning attitude, and gender, while the second factor suggested three types of tasks that could elicit the use of CSs in classrooms: information gap, reasoning gap, and opinion gap activities. Our discussion led to the conclusion that assigning peers to college/post-secondary learners with autism, based on their personal profiles and elaborating on the instructions for assigned tasks, would better prepare them to participate in peer interaction-based activities in the EAL classroom. In addition, it was suggested that future research investigate inclusive EAL classrooms that include learners with special needs.